Linking Strategic Planning Participation to Budgetary Slack: Evidence from Procedural Justice and Affective Commitment - Risya Khaerun Nisa; M. Halim; Ziad Esa Yazid (Hasanuddin Economics and Business Review, 2025)
This study explores how managerial involvement in strategic planning influences the tendency to create budgetary slack, focusing on the mediating roles of perceived procedural justice and affective commitment. Addressing a gap in the budgeting literature—which often prioritizes participative budgeting over strategic-level involvement—the research surveyed mid- to upper-level managers across various industries in Indonesia who were engaged in both strategic planning and budgeting activities. Using Partial Least Squares Structural Equation Modeling (PLS-SEM), five hypothesized relationships were tested. The results reveal that participation in strategic planning significantly enhances managers’ perceptions of procedural justice and their affective commitment to the organization. In turn, these two factors negatively affect the inclination to create budgetary slack, indicating that fairness and emotional attachment play critical roles in curbing opportunistic behavior during budgeting. All hypotheses were statistically supported, reinforcing the theoretical framework. By integrating social exchange theory and self-determination theory, this study contributes to the management accounting field by providing a deeper understanding of the ethical dynamics underlying budgeting practices. Practically, the findings suggest that organizations should embed inclusive and fair processes in strategic decision-making to foster commitment and reduce dysfunctional budgeting behaviors.